The Relationship Between Emotional Intelligence and Military Leadership Effectiveness - Wan Edenin, Wan Mahsin (2010)
The purpose of this study is to determine the relationship between Emotional Intelligence and Military Leadership Effectiveness whereby the Fourth Battalion, Royal Ranger Regiment (4 RRR) were used as a unit of analysis. The variables studied were Emotional Intelligence (consists of five dimensions) and Demography Factors (consists of four factors) as independent variables and Leadership Effectiveness as dependent variable (consists of ten items). A total of 300 sets of questionnaires were distributed to personnel of the 4 RRR and the returned feedback were 280 respondents (93.3%) which could be utilized for further analysis. The result of the survey was analyzed by using Statistical Package for social Science (SPSS) version 12. 'There were few analysis has been conducted namely frequency, reliability, descriptive, correlation and one way anova analysis. The result of analysis indicated that there is no relationship between Emotional Intelligence and Leadership Effectiveness. Meanwhile, there were also no significant differences between demographic factors to leadership effectiveness.